Spirometra in Ptyas mucosus Snake in Sidoarjo, Indonesia - Pranashinta, Garindra Tiara; Suwanti, Lucia Tri; Koesdarto, Setiawan; Poetranto, Emmanuel Djoko (KnE Life Sciences, 2017)
Currently snake is not only limited as performing animals, medicine, food and raw materials factories but also as pets. One of the famous snakes found in Indonesia is Ptyas mucosus. Snake is a port of the various parasitic zoonoses and unzoonoses. In P. mucosus also frequently reported cases of occurrence sparganosis. Sparganosis is a parasitic infection caused by the larvae spirometra or called spargana. The aim of this reasearch to study of the morphology of Spirometra in P. Mucosus snake from snakes collector in Sidoarjo, East Java. Identification adult worm and larvae in wet prepararat using a stereo microscope. Identification with Carmine staining and clearing with Glycerin using a light microscope with a magnification of 40x and 100x. The result found that P. mucosus was infected by larva of Spirometra. Sixty snakes were observed and 41 snakes were positively infected by the spargana (68%). Spargana found in musculus and subcutaneous snake P. Mucosus. Spargana are flat and thin white worms. They were like a ribbon. They are often found in groups in almost all parts of subcutaneous and musculus.The average length is 10cm, with average body width is 0,3cm. This is the first case report of sparganosis infection in P. mucosus in Indonesia. The discovery of P. mucosus sparganosis is a warning to the public to be more careful and aware in consuming snake because Spirometra sp. is one of parasitic zoonoses. Key Word: Spirometra, Ptyas mucosus, sparganosis.